15 An innovative intervention to improve respectful maternity care in three districts in ethiopia. (25th November 2019) - Jembere, Birkety; Alemu, Haregeweyni; Kassa, Munir; Mathewos, Kedest; Abate, Mehiret; Bitewulign, Befikadu; Njkou, Kendra; Zelalem, Meseret; Prose, Neil; Magge, Hema
Abstract : Background: Disrespect and abuse (D&A) during childbirth are major violations of human rights and often deter women from accessing skilled delivery. In Ethiopia, D&A has been documented to occur in 49.4% of mothers delivering in health facilities. Objectives: To describe the development, implementation and results of a novel intervention to improve Respectful Maternity Care (RMC) in three districts in Ethiopia. Methods: As part of a national initiative to reduce maternal and perinatal mortality in Ethiopia, we developed a novel RMC training module with three core components; testimonial videos, didactic session on communication, and onsite coaching to devise local solutions that enhance RMC. We implemented these in three districts in each of Oromia; Southern Nations, Nationalities, and Peoples' and Tigray regions as of February 2017. We deployed mixed methods to assess effectiveness of the approach. Measures of births with privacy and birth companion from a 27-month data from 20 health facilities were analyzed using STATA version 13 for interrupted time series. Facilitated discussion with health care providers was held to assess feedback. Results: Significant improvement with regression coefficients ranging from 0.18 to 0.77 was noted following the RMC training, which was sustained beyond the project intervention. Facilitated discussion showed improved understanding of patients' perspectives and the psychosocial needs of their clients. Conclusions: This study suggests that use of testimonial videos are especially helpful as they remind providers of the need to treat mothers with dignity and helped them reflect on potential root causes for this type of treatment and develop effective solutions.